A Study on Impact of Natural Immunostimulants on Immune Response of Catla Catla: Enhancing the immune response of Catla Catla using natural immunostimulants (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In recent years, the trend of aquaculture is growing in India at a rapid speed. Fish culturists have to face the common disease found in the fishes these days. Hence, it needs to adopt a good management practice to keep a fish healthier. The demand of natural immunostimulants is among the fish culturists as these stimulants are very useful to prevent the fish diseases.The natural immunostimulants are supposed to be eco-friendly as they are easily bio-degradable and not harmful for the human and environment. Immunostimulant is generally used in vaccines so as to enhance the immune response. Hence, it consequently improves the ability of the fishes to protect themselves from the diseases.Fishes were divided into 2 groups one received control diet and another received Plumbago rosea incorporated diet for 14 days. The haematological parameters and serum protein were estimated between control and experiment. There is An increase in TEC (P less than 0.05) and TLC (P less than 0.05) in the immunostimulant administered (IS) diet was observed.Increase in lymphocyte count was noted in immunostimulant incorporated diet. Remarkable increase in Hb from 6.2 to 8g% and serum protein level from 0.4to 0.5g% was observed in experimental fishes. The immunostimulant administered Catla catla when challenged with Aeromonas hydrophila showed a decrease in TEC and an increase in TLC. Increase in lymphocytes was also noted.